Reassessment of sustainable rural tourism strategies after COVID-19 - Kürüm Varolgüneş, Fatma; Çelik, Faysal; Del Río-Rama, María de la Cruz; Álvarez-García, José (Frontiers in Psychology, 2022)
This study aimed to develop indicators that measure rural tourism destinations in a sustainable framework during the COVID-19 process. In order to achieve this goal, the A’WOT and TOWS hybrid method was used in the study. In line with this goal, the priority order was calculated by determining the factors for strengths, weaknesses, threats and opportunities. Once these factors have been identified, strategies have been developed to build on strengths and eliminate weaknesses, while taking advantage of the opportunities and countering threats. In the study, Gökçeada-Turkey, which has recently come to the fore with its rural tourism potential, has been considered as a destination area, and strategies have been developed that adopt sustainable and responsible tourism approaches and increase the roles and capabilities of local communities. The results obtained in the study are expected to be meaningful for other rural destinations that are similar to Gökçeada.